Analysis Of The Electromagnetic Wave Produced By Partial Discharge Measured Using Loop Antenna In Air Insulation - Michael Stevano Sinurat; Farida Gultom (Institute of Computer Science (IOCS), 2023)
This study discusses the measurement of partial discharge in air insulation. Partial Discharge measurement is very important to know the condition of electrical equipment. Partial discharge causes are not only old equipment, but also from set-up errors and insulation problems. In this research, partial discharge measurement is using non-electric method. The non-electric method uses a loop antenna sensor that detects electromagnetic waves generated by partial discharge. Modeling the occurrence of partial discharge with a needle-plate electrode at a distance of 1 cm with air insulation. Partial discharge measurement parameters include Background Noise (BGN) measurements, Partial Discharge Inception Voltage (PDIV) and Partial Discharge Waveforms. The different parameters of each discharge were analyzed based on the given voltage level. The resulting data is a discharge wave obtained from an oscilloscope. The resulting data is processed using origin software so that it can determine the characteristics of the amplitude, duration of rise time and fall time of the discharge that occurs. From the results, it is known that the amplitude and duration of the rise time and fall time is greater at discharge with a higher voltage. The discharge characteristics depend on the applied voltage.